Evaluation of Dose Appropriateness in Patients Congestive Heart Failure and Comorbid Chronic Kidney Disease at RSUD Kabupaten Kediri - Ela Agustin; Shofiatul Fajriyah; Esti Ambar Widyaningrum; Adinda Sheisella Putri; Kumala Sari Poespita Dewi Wahyuni (SOCIAL CLINICAL PHARMACY INDONESIA JOURNAL, 2026)
Congestive heart failure (CHF) is a chronic condition requiring long-term therapy. Patients with heart failure accompanied by comorbid chronic kidney disease (CKD) require dose adjustment to prevent drug toxicity. This study aimed to determine the therapeutic profile and dosing appropriateness among patients with congestive heart failure and comorbid CKD hospitalized at RSUD Kabupaten Kediri during the January–December 2022 period. This study employed a retrospective observational design using medical record data with a total sampling technique, resulting in 72 eligible patients. Dose appropriateness was evaluated based on estimated glomerular filtration rate (eGFR) calculated using the Cockcroft–Gault equation and compared with recommendations from The Renal Drug Handbook. The results indicate that the majority of samples in this study were female (54.17%) and aged 45–54 years (41.67%). Most patients had additional comorbidities (80.56%), with anaemia being the most prevalent concomitant condition. Based on CKD staging, the majority of patients were classified as stage 5 CKD (77.78%). Combination therapy involving two medications was the most common treatment pattern (30.57%), with a diuretic plus ARB combination being the most frequently prescribed regimen. The evaluation of dosing appropriateness demonstrated that 69 patients (95.83%) received doses adjusted appropriately to their renal function, while 3 patients (4.17%) received inappropriate dosing. Inappropriate use was identified in prescriptions of spironolactone and acarbose, which should be avoided in patients with low eGFR values. In conclusion, most patients with congestive heart failure and comorbid CKD received therapy with doses appropriately adjusted to renal function. However, cases of inappropriate dosing were still identified, which may increase the risk of adverse effects.